Water Management in New Zealand's Canterbury Region A Sustainability Framework - Jenkins, Bryan R. (Global Issues in Water Policy,, 2018)
The book is designed to achieve two major purposes. The first is to describe the developments in water management policy in the Canterbury Region of New Zealand. The strategic approach, the collaborative engagement, and, the nested adaptive systems approach represent a paradigm shift in water management in New Zealand. The second is to delineate the sustainability framework that underpins the Canterbury approach. The framework is based on the concept of developing sustainability strategies to address critical failure pathways. While the focus of the book is on Canterbury, comparative applications of the framework to issues in other parts of New Zealand and international issues are proposed. The book can be used in at least two ways. The first is the application of a sustainability framework to the management of water in Canterbury region. The second is the exposition of a sustainability framework that can be applied to the management of water in a region with the application to Canterbury as an illustrative case study.